Plants accumulate abscisic acid after Ralstonia solanacearum infection for enhanced dehydration tolerance and plant resistance - Wang, Yao; Yan, Min; Wang, Anbin; Ma, Xingjun; Tian, Weiqiang; Liu, Ying; Zhu, Liquan; Ding, Wei; Li, Shili (Frontiers in Plant Science, 2025)
Plants will display typical dehydration and wilting symptoms after Ralstonia solanacearum infection. Many studies have shown that abscisic acid (ABA) has been implicated in wilting, but the role of ABA after R. solanacearum infection remains largely unexplored. The plant water potential and endogenous ABA content of tobacco plants were investigated after R. solanacearum infection, and we assessed the preliminary mechanisms and control effect of exogenous ABA on tobacco bacterial wilt. Here we show that R. solanacearum can reduce leaf water content (LWC) and leaf water potential (Ψleaf) and promote the accumulation of ABA on leaves. Notably, foliar spraying 0.78 mg/L ABA could alleviate the wilting by increasing Ψleaf and decreasing the stomatal size, stomatal conductance (Gs), and transpiration rate (Tr). Furthermore, 0.78 mg/L ABA application promoted plant growth, reduced the colonization of R. solanacearum, increased the activities of defense enzymes, upregulated the expression of JA/ET-related and ROS-related genes, and suppressed the expression of SA-related gene. Moreover, 0.78 mg/L ABA could reduce the incidence of tobacco bacterial wilt, with the control efficiency reaching up to 54.94% at 11 dpi, significantly higher than that of benzothiazole (BTH) with 19.33%. Our findings provided a new result for exogenous ABA controlling tobacco bacterial wilt by reducing water loss and enhancing plant resistance.